Tissue alterations in the Guinea pig lateral prostate following antiandrogen flutamide therapy - Cordeiro, R. S.; Scarano, W. R.; Goes, R. M.; Taboga, SR (Inst Histol Embriol-conicet, 2004)
The flutamide antiandrogenic effects oil the Guinea pig male prostate morphology in puberal, post-puberal and adult ages were evaluated in the present study. Daily-treated group animals received flutamide Subcutaneous injection at a dose of 10 mg/Kg body weight for 10 days. The control group animals received a pharmacological vehicle under the same conditions. The lateral prostate was removed, fixed and processed for light and transmission electron microscopy. The results revealed all increase of the acinus diameter in the treated puberal animals and straitness in the stromal compartment around the acini. The epithelial cells exhibited cubic phenotype. In the post-puberal and adult animals, a decrease of the acinus diameter was observed, as well as an increase of the smooth muscle layer and presence of the folds at epithelium. The ultrastructural evaluation of the secretory cells in the treated group demonstrated endomembrane enlargement, mainly in the rough endoplasmic reticulum and Golgi apparatus. In addition, a decrease of the microvilli and alterations in the distribution patterns and density of the stromal fibrillar components were observed. In Conclusion, the flutamide treatment exerts tissue effects oil the lateral prostate, promoting stroma/epithelium alterations.
Keywords: lateral prostate; flutamide; antiandrogen; secretory cells